Endophytic bacterial communities of oilseed rape associate with genotype-specific resistance against Verticillium longisporum. Issue 1 (26th November 2019) - Glaeser, Stefanie P; Gabur, Iulian; Haghighi, Hossein; Bartz, Jens-Ole; Kämpfer, Peter; Snowdon, Rod; Obermeier, Christian
ABSTRACT: Associations of endophytic bacterial community composition of oilseed rape ( Brassica napus L.) with quantitative resistance against the soil-borne fungal pathogen Verticillium longisporum was assessed by 16S rRNA gene amplicon sequencing in roots and hypocotyls of four plant lines with contrasting genetic composition in regard to quantitative resistance reactions. The plant compartment was found to be the dominating driving factor for the specificity of bacterial communities in healthy plants. Furthermore, V. longisporum infection triggered a stabilization of phylogenetic group abundance in replicated samples suggesting a host genotype-specific selection. Genotype-specific associations with bacterial phylogenetic group abundance were identified by comparison of plant genotype groups (resistant versus susceptible) and treatment groups (healthy versus V. longisporum -infected) allowing dissection into constitutive and induced directional association patterns. Relative abundance of Flavobacteria, Pseudomonas, Rhizobium and Cellvibrio was associated with resistance/susceptibility. Relative abundance of Flavobacteria and Cellvibrio was increased in resistant genotypes according to their known ecological functions. In contrast, a higher relative abundance of Pseudomonas and Rhizobium, which are known to harbor many species with antagonistic properties to fungal pathogens, was found to be associated with susceptibility, indicating that these groups do not play a major role in genetically controlled resistance of oilseed rape against V. longisporum . Abstract : Endophytic bacterial communities of oilseed rape associate with genotype-specific resistance against Verticillium longisporum .